Physical activity across life stages and sleep quality in adulthood - an epidemiological study - Canhin, Daniel da Silva [UNESP]; Tebar, William R. [UNESP]; Scarabottolo, Catarina C. [UNESP]; Silva, Gabriela C.R. [UNESP]; Pinto, Rafael Z.; Gobbo, Luis Alberto [UNESP]; Oliveira, Crystian B.S. [UNESP]; Christofaro, Diego G.D. [UNESP] (Elsevier, 2021)
Objective: To analyze the association between the continuous physical activity (PA) at different life stages with sleep quality in adults. Methods: This is an observational study with a cross-sectional design. A sample of 843 adults (61.7% female) with a mean age of 56.6 (±18.3) years was randomly selected. The PA at different life stages was assessed retrospectively in childhood and adolescence, and the current PA was assessed by Baecke Physical Activity Questionnaire. Sleep quality was assessed using the Mini-Sleep Questionnaire. Variables of sex, age group, ethnicity, socioeconomic status, and current physical activity were covariates. The association between continuous PA at different life stages with sleep quality was analyzed by binary logistic regression models. Results: Overweight adults who practiced PA in adolescence were 46% less likely to have poor sleep quality when compared to those who did not practice physical activity in this life stage (Odds ratio = 0.54, p = 0.031). Adults who continued to practice PA at youth and adulthood were 49% less likely to have poor sleep quality when compared to those without continuous PA (Odds ratio = 0.51, p = 0.009). Conclusions: Poor sleep quality was negatively associated with continuous PA between youth and adulthood in overall sample and negatively associated with PA in adolescence among overweight adults.
Keywords: Adolescence; Childhood; Health; Physical exercise; Sleep